Workplace Discrimination Perceived by Venezuelan Immigrants Settled in Cúcuta, Los Patios and La Parada (Colombia) - María-Antonia Cuberos; Neida Albornoz-Arias; Carolina Ramírez-Martínez; Miguel Ángel Morffe Peraza (Social Sciences)
A form of discrimination associated with international migration is workplace discrimination. This study focused on identifying discriminatory actions in working conditions, as perceived by Venezuelan immigrants residing in Cúcuta, La Parada and Los Patios (Colombia). The goal was to determine the measures employers could implement to reduce such discriminatory actions. A quantitative, non-probabilistic snowball sampling method was adopted, followed by a survey of 177 immigrants. An exploratory and descriptive analysis of the variables under study was conducted using multivariate analysis techniques of multiple correspondences with optimal scaling. The study also explored discrimination perceived by employed and unemployed immigrants, as well as by those who had been denied work during their job search. The study concluded that to address discrimination by employers, culture should be linked to ethics and corporate social responsibility, enabling organisations to successfully raise awareness among their staff, managers and those in charge of human resource management about non-discrimination policies, equal treatment and opportunities, from design to implementation, along with necessary monitoring by Labour Inspecting Offices.